MODERASI PEMAHAMAN HIRARKI MAQĀSHID AL-SYARĪʻAH DALAM FIKIH PANDEMI PERSPEKTIF FIQH AL-AWLAWIYYĀT STUDI FATWA MUI - Siti Hajar; Ahmad Zaeni (Asy-Syari'ah, 2022)
The controversy about the al-Maqâshid al-Dlarûriyyah al-Khams hierarchy has an effect on the understanding of the Maqâshid al-Syarî'ah hierarchy in the MUI version of the Fiqh Pandemic, especially the fatwa on congregational and Friday prayers in mosques. In dzahir, the fatwa prioritizes hifdz al-nafs over hifdz al-dîn, while the majority of scholars are of the opinion that hifdz al-dîn occupies the highest hierarchy. This research aims to reveal a moderate understanding of the Maqâshid al-Syarî'ah hierarchy in Fiqh Pandemic from the perspective of Fiqh al-Awlawiyyât. This research is qualitative by using Istiqrâ̕, Muqâranah and Tawtsîqî methods. The results of this study are: first, the al-Tarjîh rule used by the theocentric group allows for a middle way to bring together views between theocentric and anthropocentric groups in determining the Maqâshid al-Syarî'ah hierarchy; second, Fiqh al-Awlawiyyât is a comprehensive instrument to determine the Maqâshid al-Syarî'ah hierarchy in Pandemic Fiqh, because it accommodates the rules of al-Tarjîh, Fiqh al-Muwâzanah and Fiqh al-Taisîr wa Raf' al-Haraj, even in harmony with Fiqh al-̒Adzâr through Qiyâs Awlawî; third, Fiqh al-Awlawiyyât becomes a middle ground for the controversy between theocentric and anthropocentric groups in the context of the Maqâshid al-Syarîʻah hierarchy. In conclusion, the Maqâshid al-Syarî'ah hierarchy in Pandemic Fiqh with the priority of hifdz al-nafs over hifdz al-dîn is set moderately by using Fiqh al-Awlawiyyât.Kontroversi tentang hirarki al-maqāshid al-dlarūriyyah al-khams berpengaruh pada pemahaman hirarki Maqāshid al-Syarī’ah dalam Fikih Pandemi versi MUI, khususnya fatwa tentang shalat Jama’ah dan Jum'at di masjid. Secara dzahir, fatwa tersebut mendahulukan hifdz al-nafs atas hifdz al-dīn, sedangkan Jumhūr ulama berpendapat bahwa hifdz al-dīn menempati hirarki tertinggi. Kajian ini bertujuan untuk mengungkap pemahaman moderat tentang hirarki Maqāshid al-Syarī’ah dalam Fikih Pandemi perspektif Fiqh al-Awlawiyyāt. Penelitian ini bersifat kualitatif dengan menggunakan metode Istiqrâ̕, Muqāranah dan Tawtsīqī. Hasil penelitian ini adalah: pertama, kaidah al-Tarjīh yang digunakan kelompok teosentris memungkinkan adanya jalan tengah mempertemukan pandangan antara kelompok teosentris dan antroposentris dalam penentuan hirarki maqāshid al-syarī’ah; kedua, Fiqh al-Awlawiyyāt merupakan instrumen komprehensif untuk menentukan hirarki Maqāshid al-Syarī’ah dalam Fikih Pandemi, karena ia mengakomodir kaidah al-Tarjīh, Fiqh al-Muwāzanah dan Fiqh al-Taisīr wa Raf' al-Haraj, bahkan selaras dengan Fiqh al-A’dzār melalui Qiyās Awlawī; ketiga, Fiqh al-Awlawiyyāt menjadi jalan tengah bagi kontroversi antara kelompok teosentris dan antroposentris dalam konteks hirarki Maqāshid al-Syarīʻah. Kesimpulannya, hirarki Maqāshid al-Syarī’ah dalam Fikih Pandemi dengan prioritas hifdz al-nafs daripada hifdz al-dīn ditetapkan secara moderat dengan menggunakan Fiqh al-Awlawiyyāt.